Measurement of the tt̄ production cross section in pp̄ collisions at s=1.96TeV using kinematic characteristics of lepton+jets events - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
We present a measurement of the top quark pair production cross section in pp̄ collisions at s=1.96TeV utilizing 425pb-1 of data collected with the D0 detector at the Fermilab Tevatron Collider. We consider the final state of the top quark pair containing one high-pT electron or muon and at least four jets. We exploit specific kinematic features of tt̄ events to extract the cross section. For a top quark mass of 175 GeV, we measure σtt̄=6.4-1.2+1. 3(stat)±0.7(syst)±0.4(lum)pb, in good agreement with the standard model prediction. © 2007 The American Physical Society.